Penentuan tingkat polusi udara akibat kendaraan bermotor menggunakan metoda suseptibilitas magnetik di Kota Padang (Determination of the level of air pollution due to motorized vehicles using the magnetic susceptibility method in Padang City) - Wedara Yuliatri; - Mahrizal; Fatni Mufit (PILLAR OF PHYSICS, 2013)
ABSTRACT Air pollution in big cities has worried. Air pollution caused by human activities such as  industry, motor vehicles, burning of trash, and other activities. Air pollution caused by magnetic minerals is derived from engine frictions, corrosion of motor vehicle, and gas waste products of incomplete combustion. They fly with air and cause air pollution. Therefore research about determining pollution level from motor vehicles in Padang town was necessary. The purpose of this research was to determine the level of air pollution from vehicles motor. This research used 170 sample that consist of 99 topsoil samples, 31 leaf samples, and 40 bark samples. This research used Magnetic Susceptibility method. Magnetic Susceptibility method is used to determine the Magnetic Susceptibility value of sample. It is known by used Bartington Susceptbility Meter MS2B type. Measurement is done based on massa susceptibility value. After the Magnetic Susceptibility value is known, pollution level can be determined (low, medium or high). The result of measurement show average the Magnetic Susceptibility value in all street is 1023,2 × 10-8 – 1284,6 × 10-8 m3kg-1. It is included to high pollution category. The highest Magnetic Susceptibility value is at By Pass Lubuk Begalung street with high pollution level. The highest Magnetic Susceptibility value is at distance of 0 m from the roadside, thus 1 m from the roadside and 2 m from the roadside. Keywords: magnetic minerals, Air pollution, Magnetic susceptibility